When Alterations in Social Cognition Meet Subjective Complaints in Autism Spectrum Disorder: Evaluation With the “ClaCoS” Battery - Morel-Kohlmeyer, Shasha; Thillay, Alix; Roux, Sylvie; Amado, Isabelle; Brenugat, Lindsay; Carteau-Martin, Isabelle; Danset-Alexandre, Charlotte; Gaudelus, Baptiste; Graux, Jérôme; Peyroux, Elodie; Prost, Zelda; Krebs, Marie-Odile; et al. (Frontiers in Psychiatry, 2021)
Background: Deficit in social communication is a core feature in Autism Spectrum Disorder but remains poorly assessed in classical clinical practice, especially in adult populations. This gap between needs and practice is partly due to a lack of standardized evaluation tools. The multicentric Research group in psychiatry GDR3557 (Institut de Psychiatrie) developed a new battery for social cognitive evaluation named “ClaCoS”, which allows testing the main components of social cognition: Emotion Recognition, Theory of Mind, Attributional Style, and Social Perception and Knowledge. It further provides an assessment of subjective complaints in social cognition. Methods: We compared the social cognition abilities of 45 adults with Autism Spectrum Disorder without intellectual disability and 45 neurotypically developed volunteers using the “ClaCoS” battery, in order to determine its relevance in the evaluation of social cognition impairments in autism. A correlational approach allowed us to test the links between subjective complaints and objectively measured impairments for the different components of social cognition. Results: As expected, the Autism Spectrum Disorder group showed deficits in all four components of social cognition. Moreover, they reported greater subjective complaints than controls regarding their social abilities, correlated to the neuropsychological assessments. Conclusion: The “ClaCoS” battery is an interesting tool allowing to assess social impairments in autism and to specify the altered components, for a better adjustment of tailored social cognition training programs. Our results further suggest that people with Autism Spectrum Disorder have a good social cognitive insight, i.e. awareness into social cognitive functioning, and may thus benefit from social cognitive training tools.